PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM MENINGKATKAN KINERJA PADA KARYAWAN PT. CASSIA COOP - Rio Baviga (LPPM Universitas Bina Bangsa, 2024)
This study the author uses an empirical approach, namely research used to solve research problems by conducting primary data research in the field. The object of this research is PT. Cassia Coop in Koto Dumo Village, Tanah Kampung Kota Sungai Full District. The results showed that the Accounting Information System (SIA) did not have a significant effect on the Performance of PT. CASSIA COOP is proven by t count < t table (1.115 < 2.10092) then Ho is accepted and Ha is rejected, meaning that there is no significant influence between the Accounting Information System (SIA) on Performance. The magnitude of the influence of the Accounting Information System (SIA) on the Performance of PT. CASSIA COOP was 2.82%, while my side was 97.18% influenced by other variables that were not studied